Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/9678168
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cells in Circulation and Tumor Microenvironment of Colorectal Cancer Patients with Early and Advanced Disease Stages

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogenous population of cells that have been implicated in the development of an immunosuppressive environment, which promotes tumorigenesis and tumor progression. Numerous studies have reported expansion of MDSCs in circulation and the tumor microenvironment (TME) of cancer patients. However, due to the heterogenic nature of MDSCs and the different approaches for their identification, their detailed characterization and impact on disease progression in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…Studies in CRC patients also show that human MDSCs enhance CRC cell stemness [ 171 ], which accelerates faster cancer cells proliferation. Toor et al showed that levels of tumor-infiltrating MDSC were increased in patients with high tumor budding and advanced stage of CRC suggesting their potential roles in metastasis [ 173 ].…”
Section: Reviewmentioning
confidence: 99%
“…Studies in CRC patients also show that human MDSCs enhance CRC cell stemness [ 171 ], which accelerates faster cancer cells proliferation. Toor et al showed that levels of tumor-infiltrating MDSC were increased in patients with high tumor budding and advanced stage of CRC suggesting their potential roles in metastasis [ 173 ].…”
Section: Reviewmentioning
confidence: 99%
“…Generally, MDSCs in human are defined as CD33 + CD11b + HLA-DR low cells and are classified into two primary subgroups based on differences in cell morphology and cell-surface markers: granulocytic (polymorphonuclear) CD33 + CD11b + HLA-DR low CD15 + cells (G-MDSCs) and monocytic CD33 + CD11b + HLA-DR low CD14 + cells (M-MDSCs) [ 70 73 ]. More recently, an additional subgroup has been identified as CD33 + CD11b + HLA-DR low CD14 − CD15 − , and they are named immature or early-stage MDSCs (e-MDSCs) [ 72 , 74 , 75 ].…”
Section: Myeloid-derived Suppressor Cells (Mdscs)mentioning
confidence: 99%
“…MDSC subpopulations of monocytic and granulocytic cells have been identified and characterized in different human cancers [ 82 85 ]. They inhibit antitumor immune responses [ 85 87 ], and as a result, cancer cells continue to evolve [ 75 ].…”
Section: Myeloid-derived Suppressor Cells (Mdscs)mentioning
confidence: 99%
“…Meanwhile, M2 macrophages, polarized by IL-4 and IL-13 favor tumor promotion and create an immuno-subversive environment by interfering with T cell functionality [71]. In addition to these, MDSCs are considered as one of the major immunosuppressive cells, which abundantly exist in the TME [72]. MDSCs are heterogenous population including two major subtypes; polymorphonuclear (PMN-MDSC) or granulocytic (G-MDSCs) and monocytic (M-MDSCs), which have potent immunosuppressive characteristics and favor tumorigenesis and progression [73,74].…”
Section: Immune Cellsmentioning
confidence: 99%